Metalinguagem e dialogismo em Jorge Furtado: saneamento básico e outras obras - Barbosa, Afonso Manoel da Silva (2017)
The audiovisual texts of Jorge Furtado, in significant part, have engagements that stand out for the way in which they discuss artistic work itself, pointing out their constitutive devices in a self-referential view, and how they give visibility to a variety of statements that come not only from the audiovisual language, but also originating from other discursive fields, such as literature, theater and the plastic arts. The metalinguistic character and the predisposition to reveal and give relevance also to its dialogical aspect are allied to comic mechanisms, crossing a considerable number of Furtado productions, in the scope of short and feature films, as well as works for television. This main interest in this research is to analyze metalinguistic data and, in this context, aspects of metafictionality, also discussing the dialogic construction emphasized in the discursive plurality of the feature film Saneamento básico, o filme. We are interested in observing the work of 2007, directed and scripted by Jorge Furtado, in its metalinguistic portion, pointing out his predisposition to unveil the fictional discourse when using the representation of a countryside community in his first contact with filmmaking. In this context, the study should also focus on this duplication that unfolds from the use of a metafictional process within the narrative of the film and elements of the construction of the comic. In addition, we must examine how the creative impulse is interwoven with elements such as internalized knowledge and artistic sensitivity - latent, veiled and revealed - that is gradually developed in the characters. We also see the need to examine other productions directed and scripted by Furtado and partners, analyzing specific data of these works, especially from issues related to metalanguage and dialogism, tracking in this sense narrative and stylistic recurrences that help us in understanding the production of the director-writer, in order to contribute to the verticalization of the central object of the corpus of our research, the feature film Saneamento básico.